2021
DOI: 10.1111/tpj.15528
|View full text |Cite
|
Sign up to set email alerts
|

A chromosome‐scale Gastrodia elata genome and large‐scale comparative genomic analysis indicate convergent evolution by gene loss in mycoheterotrophic and parasitic plants

Abstract: Summary Mycoheterotrophic and parasitic plants are heterotrophic and parasitize on fungi and plants, respectively, to obtain nutrients. Large‐scale comparative genomics analysis has not been conducted in mycoheterotrophic or parasitic plants or between these two groups of parasites. We assembled a chromosome‐level genome of the fully mycoheterotrophic plant Gastrodia elata (Orchidaceae) and performed comparative genomic analyses on the genomes of G. elata and four orchids (initial mycoheterotrophs), three para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…Thus, gene loss became more severe as the degree of parasitism increased. Considering our data of gene loss in Orobanchaceae and the previous published data from Orchidaceae (41) and Sapria himalayana (16), in parasitic plants and mycoheterotrophic plants, which are all heterotrophs, the degree of gene loss and parasitism seems to be well positively correlated as well. Accordingly, heterotrophic plants could be divided into four classes with increasing levels of heterotrophy and degrees of gene loss: in the first class, heterotrophs with 2-3% gene loss are facultative hemiparasites; in the second class, heterotrophs with 6-7% gene loss require hosts to complete certain developmental stages, and these are obligate hemiparasites and initial mycoheterotrophic plants, such as most species of Orchidaceae; in the third class, heterotrophs lost 13-15% genes, and these are holoparasites or full mycoheterotrophs with vegetative organs, such as Cuscuta, Orobanche, and Gastrodia; in the fourth class, gene loss is over 30% and these are endoparasites with only reproductive organs, such as Sapria himalayana.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, gene loss became more severe as the degree of parasitism increased. Considering our data of gene loss in Orobanchaceae and the previous published data from Orchidaceae (41) and Sapria himalayana (16), in parasitic plants and mycoheterotrophic plants, which are all heterotrophs, the degree of gene loss and parasitism seems to be well positively correlated as well. Accordingly, heterotrophic plants could be divided into four classes with increasing levels of heterotrophy and degrees of gene loss: in the first class, heterotrophs with 2-3% gene loss are facultative hemiparasites; in the second class, heterotrophs with 6-7% gene loss require hosts to complete certain developmental stages, and these are obligate hemiparasites and initial mycoheterotrophic plants, such as most species of Orchidaceae; in the third class, heterotrophs lost 13-15% genes, and these are holoparasites or full mycoheterotrophs with vegetative organs, such as Cuscuta, Orobanche, and Gastrodia; in the fourth class, gene loss is over 30% and these are endoparasites with only reproductive organs, such as Sapria himalayana.…”
Section: Discussionsupporting
confidence: 79%
“…Although photoreceptors can regulate flowering time, sense day length and maintain the circadian rhythm of plants, it has been shown that genes involved in circadian clock and flowering-time regulation tend to be lost in heterotrophic species, as has also been observed for G. elata and C. australis 45 . Photoreceptors also mediate various physiological and developmental processes of plants, such as phototropism, leaf expansion, chloroplast movement and neighbour perception 44 , suggesting that the loss of some photoreceptor genes might have had a cascading effect on the general biological response to light, such as leaf and root development.…”
Section: Resultsmentioning
confidence: 86%
“…Compared to G. elata , genes related to regulation of autophagy and nitrogen compound transport increased in G. menghaiensis (Supplementary Tables S 18 , S 19 and S 20 ). Compared to P. equestris [ 33 ] (29,334 PCGs), D. officinale (29,099 PCGs), G. elata [ 9 , 29 ] (18,950–21, 115PCGs), and A. shenzhenica [ 34 ] (21,676 PCGs), G. menghaiensis has a relatively small proteome (17,948 PCGs), making it the smallest proteome thus far among angiosperms (Supplementary Table S 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most species of Gastrodia , such as G. menghaiensis (Supplementary Figure S 1 a-b), form well-developed mycorrhizal roots, whereas other species, such as G. elata (Supplementary Figure S 1 c), are rootless with their fungal associate directly connected to their tubers [ 14 , 26 , 27 ]. To date, G. elata has the smallest known angiosperm genome, containing approximately 18,969 protein-coding genes [ 9 , 28 ] (but see [ 29 ]) with some genes families associated with its mycoheterotrophic lifestyle, such strigolactone signaling and digestion of hyphae, expanded.…”
Section: Introductionmentioning
confidence: 99%